(untitled) (Eurasian Journal of Learning and Academic Teaching, 2021)
The purpose of this work is to consider the subjective characteristics of the teacher’s personality, and then we will touch on only the first three groups of the structure of subjective properties. The place and functions of the teacher in society, the requirements of society and social expectations in relation to the personality and activities of the teacher are also considered.